Erythrina mulungu Alkaloids Are Potent Inhibitors of Neuronal Nicotinic Receptor Currents in Mammalian Cells - Setti-Perdigao, Pedro; Serrano, Maria A. R. [UNESP]; Flausino, Otavio A. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Guimaraes, Marilia Z. P.; Castro, Newton G. (Public Library Science, 2013)
Crude extracts and three isolated alkaloids from Erythrina mulungu plants have shown anxiolytic effects in different animal models. We investigated whether these alkaloids could affect nicotinic acetylcholine receptors and if they are selective for different central nervous system (CNS) subtypes. Screening experiments were performed using a single concentration of the alkaloid co-applied with acetylcholine in whole cell patch-clamp recordings in three different cell models: (i) PC12 cells natively expressing alpha 3* nicotinic acetylcholine receptors; (ii) cultured hippocampal neurons natively expressing alpha 7* nicotinic acetylcholine receptors; and (iii) HEK 293 cells heterologoulsy expressing alpha 4 beta 2 nicotinic acetylcholine receptors. For all three receptors, the percent inhibition of acetylcholine-activated currents by (+)-11a-hydroxyerysotrine was the lowest, whereas (+)-erythravine and (+)-11a-hydroxyerythravine inhibited the currents to a greater extent. For the latter two substances, we obtained concentration-response curves with a pre-application protocol for the alpha 7* and alpha 4 beta 2 nicotinic acetylcholine receptors. The IC50 obtained with (+)-erythravine and (+)-11a-hydroxyerythravine were 6 mu M and 5 mu M for the alpha 7* receptors, and 13 nM and 4 nM for the alpha 4 beta 2 receptors, respectively. Our data suggest that these Erythrina alkaloids may exert their behavioral effects through inhibition of CNS nicotinic acetylcholine receptors, particularly the alpha 4 beta 2 subtype.